Pembuatan Tungku Pembakaran Logam - Putra, Afrionaldi; Mukhnizar, Mukhnizar; Selviyanty, Veny; Abu, Risal; Afdal, Afdal (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
Current technological advances have produced many products that aim to make human work easier. One of them is an iron burning tool that uses a blower as a tool used to increase or enlarge the air or gas pressure that will flow into the combustion container (furnace). The blower used is a 2 inch snail blower as a tool to increase the air pressure so that the air that is supplied can enlarge the burning flame. The furnace used is a drum coated with heat-resistant cement which can withstand the heat of the combustion fire so that the furnace does not melt. The frame materials used are hollow iron measuring 40 x 40 and angle iron measuring 40x40. For combustion, it uses coal as the main fuel and the blower itself as an air distributor so that it can produce the desired fire. Based on the test results in a metal burning furnace, a temperature of 340°C can be obtained as planned so that by heating the metal, various types of equipment can be formed as desired